Dynamic Impedance Spectroscopy of Nickel Hexacyanoferrate Thin Films. Issue 21 (21st October 2019) - Erinmwingbovo, Collins; Koster, Dominique; Brogioli, Doriano; La Mantia, Fabio
Abstract: Invited for this month's cover picture is the Energy Storage and Conversion Systems' Group of the University of Bremen (Germany). The cover picture shows the application of dynamic multi‐frequency analysis (DMFA) for studying the kinetics of nickel hexacyanoferrate thin film, which is unstable in its oxidized form. The image shows the two‐step intercalation mechanism for the deintercalation of univalent cations in nickel hexacyanoferrate thin film. Read the full text of the Article at 10.1002/celc.201900805 . Abstract : "DMFA allows for the acquisition of time‐resolved impedance, making it suitable for studying unstable or evolving electrochemical systems. DMFA is used to study the kinetics of a nickel hexacyanoferrate thin film, which is unstable in its oxidized form…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.201900805 .